The Use of Rubrics in Higher Education and Competencies Evaluation. Scientific Study about Characteristics of Rating Scales Used by Professors - Velasco-Martínez, Leticia Concepción; Tójar-Hurtado, Juan Carlos (My University, 2014)
Competency-based learning in Spain has achieved a reconfiguration of higher education to meet the current demands of training. In this regard, institutions and different university regulations promote a "constructive alignment" of the essential elements from the curriculum (Biggs, 2005), giving to the competencies the role of curricular model which gives coherence to the new design of degrees. In the university context, scoring rubrics are considered an innovation tool to collect evidences of competency acquisition (Baryla, Shelley and Trainor, 2012, White, 2011; Cebrián, 2012; Andradre and Reddy, 2010). Its potential lies in the ability for issuing adjusted valuations about the quality of student’s works in a wide range of subjects or tasks (Blanco, 2008). Regarding the type of rubric, Blanco (2008, 176) notes that "the selection form one kind or another of rubric depends mainly on the use you want to give to the outcomes, that is, if the emphasis is more focused on the formative aspects or on the summative ones. Other factors to consider: the required time, the nature of the task itself or the specific performance criteria which are being observed”. Based in these assumptions it is studied: What kinds of rubrics are used by teacher: analytic (formative) or holistic (summative)? Do professors know the pedagogical and techniques requirements needed to design rubrics?
Keywords: Competencia en educación; Enseñanza superior; Rubric; Higher Education; Competencies; Professors